Objective and subjective career success: individual, structural, and behavioral determinants on European hybrid workers - Hildred, Kiall; Piteira, Margarida; Cervai, Sara; Pinto, Joana Carneiro (Frontiers in Psychology, 2023)
In the current worldwide labor context, where a disruption took place and employees experience greater flexibility in their work location, no longer working only from the office, it is, more than ever, key to investigate how the changes in work-life have altered the path for a successful career. The goal of this study is to investigate the effects of a set of individual (gender, academic degree, marital status, children), structural (type and size of the company employment status), and behavioral determinants (authenticity, balance and challenge from the Kaleidoscope Career Model [KCM]) on the objective and subjective success of a sample of 739 European hybrid workers. Participants fulfilled an online assessment protocol developed in English and translated to Portuguese, Spanish, Italian, French and German. Results indicate that higher ages, higher educational levels, being married, having children, working full-time, and accepting higher levels of challenge are predictors of higher objective success. In turn, being a male, with children and accepting higher levels of challenge are predictors of higher subjective success, while searching for authenticity and balance are responsible for lower levels. This study makes a unique contribution to the extant research on hybrid workers’ careers, specifically about the importance of key decision-makers in companies having knowledge about the impact that different variables can have on their employees’ success.